Where the girls are not: Households, teachers, and the gender gap in early math achievement - Pedro M. Carneiro; Yyannú Cruz-Aguayo; Norbert Rüdiger Schady (Inter-American Development Bank (IDB), 2017)
We study the determinants of math achievement among children in early elementary school using data from a unique experiment. We find steep socioeconomic gradients and a substantial boy-girl gap in math test scores. However, among children of mothers with university education, there is no difference in the math achievement of girls and boys, which suggests that maternal education specifically, and home environments generally, are important. There is no evidence that teacher quality affects the boy-girl differences in early test scores, regardless of whether we measure quality on the basis of classroom effects, teacher effects, or the observed interactions between teachers and children.
Keywords: I21; 330; test scores; teachers; gender